Superalloys 2008 (Eleventh International Symposium) 2008
DOI: 10.7449/2008/superalloys_2008_527_533
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Low Cycle (Notch) Fatigue Behaviour at Temperature in Single Crystal Turbine Blade Materials

Abstract: The scatter in notch fatigue lifetimes of CMSX4 at 650˚C and 725˚C in air and vacuum and with Rene N5 in air at 650˚C is compared under the same (plastic) notch strain range levels. Rene N5 shows shorter lifetimes under equivalent conditions and always exhibits multiple initiation sites. The role of interdendritic porosity in initiating fatigue in both alloys is identified, and the number of initiation sites is found to directly affect fatigue life. In air in CMSX4 and Rene N5, subsurface pores initiate fatigu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 10 publications
1
5
0
Order By: Relevance
“…The theoretical and the finite element analyses showed that the subsurface holes exhibit higher stress concentrations than the surface notches for which SCF ≈ 3. This is in agreement with the experimental findings that subsurface pores are the sites of crack initiations [7] - [10]. It was also observed that, for the 5:1 radii ratio, the interaction effect of SCF vanishes at notch-hole gap of 10a and above.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The theoretical and the finite element analyses showed that the subsurface holes exhibit higher stress concentrations than the surface notches for which SCF ≈ 3. This is in agreement with the experimental findings that subsurface pores are the sites of crack initiations [7] - [10]. It was also observed that, for the 5:1 radii ratio, the interaction effect of SCF vanishes at notch-hole gap of 10a and above.…”
Section: Discussionsupporting
confidence: 91%
“…Subsurface and close to surface porosities have been investigated experimentally and considered as sources of fatigue failures and sites of crack initiation by several authors [7][8][9][10]. Reed and Miller assessed the fatigue behaviour of turbine materials at elevated temperatures in air and vacuum environments.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fatigue life and fatigue deformation mechanisms of the nickel-based SC superalloys have been confirmed to be governed by the chemical composition, the size and volume fraction of γ' phase and loading conditions [9][10][11][12][13][14][15][16][17]. The distinct cyclic stress responses and cracking morphology of the nickel-based SC superalloys depend on slip characteristics under various loading conditions such as strain amplitude, temperatures, oxidation and hold time [18][19][20][21].…”
Section: Introductionmentioning
confidence: 92%
“…In SX RENE ´N5, again casting pores were found to initiate fatigue cracks, though surface oxide cracks were not observed to initiate critical fatigue cracks. 5 In SX alloy, CMSX-4 at the highest temperature of 950uC cracks initiated at surface scales and propagated into the bulk of the alloy via planar growth. 6,7 The results showed that the number of surface cracks was higher in specimens subjected to out of phase (OP) TMF specimens (total 57 cracks) than in isothermal fatigue, with a total of 44 cracks; here, OP refers to where the maximum strain is reached at a minimum temperature.…”
Section: Introductionmentioning
confidence: 99%